2008
DOI: 10.1016/j.jtcvs.2007.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in postsurgical adhesion formation after cardiac surgery in a rabbit model using N,O-carboxymethyl chitosan to block cell adherence

Abstract: The application of N,O-carboxymethyl chitosan gel and solution significantly reduces the severity of postsurgical adhesion formation after cardiac surgery in the rabbit model. The inability of fibroblasts to adhere to N,O-carboxymethyl chitosan-coated surfaces suggests that N,O-carboxymethyl chitosan may act as a biophysical barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The barrier methods using bio-absorbable biopolymers released in a gel composition or in a sheet layer showed good results [11,12]. These methods are in accordance with the Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The barrier methods using bio-absorbable biopolymers released in a gel composition or in a sheet layer showed good results [11,12]. These methods are in accordance with the Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Heterologous pericardium [7], anti-inflammatory drugs [8], synthetic rubbers [9], fibrinolytic agents [10] and biopolymers [11,12] are examples of therapies explored for such purpose.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis concerning the function of O-CMC is supported by several studies. An in vitro study demonstrated that few of fibroblasts and macrophages could adhere to N,O-CMC-coated plates, 11 implying that the chitosan derivative inhibits the adhesion of inflammatory cells to the ECM of injured tissues. In another study, intranasal application of water-soluble chitosan was shown to attenuate infiltration of inflammatory cells and markedly decrease production of inflammatory cytokines such as tumor necrosis factor-α and interleukin 6.…”
Section: Discussionmentioning
confidence: 99%
“…This water-soluble chitosan derivative has been shown to reduce postoperative adhesion development, [8][9][10] which may act as a biophysical barrier and block the adherence of inflammatory cells. 11 Another chitosan derivative, O-carboxymethyl chitosan (O-CMC), developed by carboxymethylation of chitosan's oxygen centers, also exhibits remarkable water-solubility and bio-compatibility. 12 Little is known, however, of the potential of O-CMC to protect against adhesion formation.…”
mentioning
confidence: 99%
“…Radiographic evidence of bone regeneration by exploiting NNDCMchitosan for the delivery of bone morphogenetic protein to bones in human patients undergoing apicectomies and avulsions was observed (Mattioli-Belmonte et al, 1999). The efficacy of NOCMchitosan to reduce post operative adhesion formation has also been demonstrated in rabbit by a cardiac injury model and an abdominal surgery model (Zhou, Liwski, Elson, & Lee, 2008).…”
Section: Apoptosis Inhibitory Activitymentioning
confidence: 98%